Questionable Research Practices and Open Science in Quantitative Criminology - Chin, Jason M. (Journal of quantitative criminology, 2023)
Objectives Questionable research practices (QRPs) lead to incorrect research results and contribute to irreproducibility in science. Researchers and institutions have proposed open science practices (OSPs) to improve the detectability of QRPs and the credibility of science. We examine the prevalence of QRPs and OSPs in criminology, and researchers’ opinions of those practices. Methods We administered an anonymous survey to authors of articles published in criminology journals. Respondents self-reported their own use of 10 QRPs and 5 OSPs. They also estimated the prevalence of use by others, and reported their attitudes toward the practices. Results QRPs and OSPs are both common in quantitative criminology, about as common as they are in other fields. Criminologists who responded to our survey support using QRPs in some circumstances, but are even more supportive of using OSPs. We did not detect a significant relationship between methodological training and either QRP or OSP use. Support for QRPs is negatively and significantly associated with support for OSPs. Perceived prevalence estimates for some practices resembled a uniform distribution, suggesting criminologists have little knowledge of the proportion of researchers that engage in certain questionable practices. Conclusions Most quantitative criminologists in our sample have used QRPs, and many have used multiple QRPs. Moreover, there was substantial support for QRPs, raising questions about the validity and reproducibility of published criminological research. We found promising levels of OSP use, albeit at levels lagging what researchers endorse. The findings thus suggest that additional reforms are needed to decrease QRP use and increase the use of OSPs.